Gastroesophageal reflux following pneumatic dilatation in achalasia - Nadir YÖNETÇİ and Serhat BOR and Mehmet İŞLER and Ahmet MUSOĞLU and Ahmet AYDIN and Hanefi ÇAVUŞOĞLU (Turkish Journal of Gastroenterology, 2020)
-